Membangun Niat Berwirausaha Mahasiswa melalui Self-efficacy dan Dukungan Lingkungan - Siyamto, Yudi; Budiningrum, Endah Wening; Wijayanti, Irine Diana Sari (Universitas Hamzanwadi, 2026)
Indonesia’s high unemployment rate, reaching 7.28 million people, highlights the urgency of strengthening student entrepreneurship as a driver of job creation. This study examines the effects of environmental support, Self-efficacy, and creativity on students’ entrepreneurial intention. Data were collected from 166 final-year students of the Yogyakarta Academy of Administrative Management and analyzed using Partial Least Squares–Structural Equation Modeling (SmartPLS). The results show that environmental support and Self-efficacy significantly influence entrepreneurial intention, while creativity has no significant effect. Moreover, Self-efficacy mediates the relationship between environmental support and entrepreneurial intention, indicating that confidence acts as a psychological bridge transforming external support into entrepreneurial drive. These findings emphasize the importance of cultivating an educational environment that fosters both confidence and social support to encourage students to create new business opportunities.